To solve the equation \( 13(6x - 9) = -33 \), follow these steps in the correct order:
-
Distribute: Multiply \( 13 \) by both terms inside the parentheses. \[ 13 \times 6x - 13 \times 9 = -33 \quad \Rightarrow \quad 78x - 117 = -33 \]
-
Add 117 to both sides: To isolate the term with \( x \). \[ 78x - 117 + 117 = -33 + 117 \quad \Rightarrow \quad 78x = 84 \]
-
Divide by 78: To solve for \( x \). \[ x = \frac{84}{78} \]
-
Simplify the fraction: Both the numerator and denominator can be divided by 6. \[ x = \frac{14}{13} \]
So the order of steps is:
- Distribute.
- Add 117 to both sides.
- Divide by 78.
- Simplify the fraction.